The need to review SHG approach through SGSY - Patne, Atul N. (2002)
The rising unemployment in the country especially in the rural areas gave rise to the formulation of the Swarna Jayanti Gram Swarojgar Yojana by the government. The scheme lays emphasis on the formation of Self-help Groups in order to provide maximum benefits to the people belonging to the Below Poverty Line category for the purpose of obtaining credit. The current article focuses on the need to review this SHG approach as there is a growing concern whether these groups have actually been able to attain economic self-sufficiency. The author, Atul Patne, IAS, Assistant Collector, Murtizapur, Akola, Maharashtra, thus suggests some proposals, wherein he has derived certain parameters of growth for the SHGs and graded them according to their importance. Thus what emerges is the increase in creditworthiness of the SHGs, as well as progress in their personal development, as bonus points have been allotted for fulfilling the conditions of literacy, group insurance and family planning, etc. - Reproduced.
Keywords: Employment